Examining the Impact of Auditors’ Narcissism and Overconfidence on Audit Quality Through Auditors’ Leadership Ability - Hemati Dehaghani, Ahmad; Mohammadi Khoshoei, Hamzeh; Saedi, Rahman (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of this study was to examine the impact of auditors’ narcissism and overconfidence on audit quality through the leadership ability of auditors. Methodology: This research is applied in terms of its purpose and employs a survey methodology with structural equation modeling for data collection. The population of this study comprises all partners and managers who are members of the Institute of Certified Accountants of Iran and were employed in auditing organizations or private firms during the year 2022. A sample of 326 individuals was randomly selected based on Cochran’s formula. Data were collected using standard questionnaires containing 84 Likert-scale questions. Descriptive and inferential analysis of the collected data and hypothesis testing were conducted using structural equation modeling (SEM) with partial least squares (PLS) approach using SPSS and PLS software. Findings: The findings indicate that the leadership ability of audit teams, led by partners and managers, has a positive and significant impact on audit quality. Furthermore, the narcissism of auditors positively and significantly affects audit quality through their leadership ability, while, according to the theory of leadership personality traits, overconfidence negatively and significantly affects audit quality through the leadership ability of auditors. Conclusion: Therefore, attention to leadership in audit teams and a moderate level of narcissism and confidence are necessary and essential for auditors in leadership positions.